The effect of Eu3+ concentration on the Y2O3 host lattice obtained from citrate precursors - Ferrari, J. L. [UNESP]; Pires, A. M. [UNESP]; Davolos, M. R. [UNESP] (Elsevier B.V. Sa, 2009)
This work presents a thermal decomposition study of the precursor resin prepared from the citrate precursor along with structural features and optical properties materials composed by Y2O3 and Eu3+ containing Y2O3 in 0.5, 3, 5 and 7 mol%. The microcrystallite sizes were estimated from the Scherrer equation. The structural and optical properties revealed that the addition of 5 mol% of Eu3+ to the Y2O3 matrix gave rise to the highest relative emission intensity which was evidenced by the luminescence intensity. The lifetime of the 0.5 mol% Eu3+-doped sample suggested two different symmetry sites for Eu3+ ions because two different lifetime values were acquired for this sample, while for phosphors doped with 3 or 5 mol% of Eu3+ ions only one similar lifetime was observed. When the concentration of Eu3+ is 0.5 and 3 mol%, the luminescence intensity is weak due to the low probability of the O2--Eu3+ charge transfer transition. on the other hand, when the concentration of the Eu3+ ions is 7 mol%, a quenching effect is evidenced. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Oxides; Heat treatment; Photoluminescence spectroscopy